Keefektifan Metode Pembelajaran Project Bassed Learning (PjBL) sebagai Pemantik Hasil Belajar Peserta Didik MTs Dalam Materi Menggambar Komik Berupa Cerita Fabel - Ayu Rayindra, Monica (STAB Kertarajasa, 2024)
The results of the preliminary study conducted at MTsN 10 Banyuwangi, along with interviews conducted with several art and culture teachers in the MGMP group in the Banyuwangi region, revealed that there are still issues with the teaching methods being used. The interview results also indicated that teachers are unable to implement effective learning approaches due to limitations in their creativity and a lack of teaching media. The problem statement in this study is how effective the Project-Based Learning (PjBL) method is in improving the learning outcomes of MTs students in comic drawing material in the form of fable stories. This study was conducted at Madrasah Tsanawiyah Negeri 10 Banyuwangi, located in Rogojampi District, Banyuwangi Regency. The study was conducted between March and May 2024. The subjects of this study were eighth-grade students at MTsN 10 Banyuwangi. This research is a mixed-methods study, using qualitative as the primary method and quantitative as the secondary method. The results of this study showed that in the small group test, large group test, and the distribution of N-Gain scores at each meeting, there was an increase. This increase is evidenced by the N-Gain score, which in the last meeting of the small group test was 0.68 (moderate category) and increased to 0.78 (high category) in the last meeting of the large group test. This indicates that the Project-Based Learning (PjBL) method is effective in improving students' learning outcomes in understanding comic drawing material.